Immediate heart-rate response to standing: simple test for autonomic neuropathy in diabetes. Issue 6106 (21st January 1978) - Ewing, D J; Campbell, I W; Murray, A; Neilson, J M; Clarke, B F
Abstract : The immediate heart-rate response to standing was measured in 22 normal controls and 25 patients with diabetes, 15 of whom had autonomic neuropathy. The response in the controls and patients without autonomic neuropathy was characteristic and consistent, with tachycardia maximal at around the 15th beat and relative bradycardia maximal at around the 30th beat. The diabetics with autonomic neuropathy, however, showed a flat response. In three controls the response was abolished with intravenous atropine but not with propranolol, showing that it is mediated through the vagus. A simplified test using routine ECGs and measuring the R-R interval at beats 15 and 30 with a ruler is easily performed as an outpatient procedure and may be used as a measure of autonomic function in diabetes.